2015
DOI: 10.1016/j.ijhydene.2015.03.124
|View full text |Cite
|
Sign up to set email alerts
|

FPGA based fault-tolerant control on an interleaved DC/DC boost converter for fuel cell electric vehicle applications

Abstract: Available online xxxKeywords: PEMFC Interleaved DC/DC converter Electric vehicle Power switch fault Fault-tolerant control Degraded operating mode a b s t r a c t In recent years, the effects of high-frequency current ripple coming from DC/DC converters on Proton Exchange Membrane Fuel Cell (PEMFC) have gained a growing interest from the international scientific community. Currently, the durability is one of the major technical challenges to PEMFC commercialization. Basing on the existing literature, the highf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…They collected experimental data and concluded that this prediction may be applied in degradation prediction for real conditions. In Reference 63 Guilbert et al highlight that FTC has the ability to reduce significantly the current ripple in the power switch faults.…”
Section: Methodsmentioning
confidence: 99%
“…They collected experimental data and concluded that this prediction may be applied in degradation prediction for real conditions. In Reference 63 Guilbert et al highlight that FTC has the ability to reduce significantly the current ripple in the power switch faults.…”
Section: Methodsmentioning
confidence: 99%
“…Guilbert et al [13,15] applied a FTC strategy to the DC/DC con verter of a PEMFC. The considered converter is made with 3 legs.…”
Section: Active Fault Tolerant Controlmentioning
confidence: 99%
“…On a Hardware-In-Loop test bench with a twin screw compressor and real time fuel cell emulation system. [15] FTC method which involve the change of the Pulse-width modulation gate control signal. The method is applied to the electric vehicle using a PEMFC stack.…”
Section: Floodingmentioning
confidence: 99%
“…The authors of [15] presented an interleaved boost topology that is robust to failures through the redundancy of the input meshes for a single power supply. Although they presented experimental results, the modeling, uncertainty, and stability analysis were missing.…”
Section: Introductionmentioning
confidence: 99%
“…15 show the output ripples obtained for nominal operation, e 2 drop, and e 3 drop respectively. It can be noticed that the ripple increased considerably as the fall in the voltages of the other sources is greater.Energies 2020, 13, 1694 18 of 22 Energies 2020, 13, x FOR PEER REVIEW 20 of 23…”
mentioning
confidence: 99%